Improving the prediction of functional recovery in older adults with stroke in geriatric rehabilitation using an inertial measurement unit combined with the Utrecht Scale for Evaluation of Rehabilitation (USER) - Jules J.M. Kraaijkamp; Margot W.M. de Waal; Niels H. Chavannes; Wilco P. Achterberg; Eléonore F. van Dam van Isselt; Michiel Punt (Journal of Rehabilitation Medicine - Clinical Communications)
Background: Prediction of functional recovery in older adults recovering from stroke is typically based on observational scales, such as the Utrecht Scale for Evaluation of Rehabilitation (USER). Objectively measuring postural sway using inertial measurement devices (IMU) may complement or improve conventional approaches. The aim of this study was to evaluate whether integrating an IMU with USER data enhances the accuracy of predicting functional recovery at discharge.